Jagged edge - Ransohoff, Martin; Marquand, Richard; Colombia Pictures; Colombia TriStar Home Video (Firm) (Culver City, California : Colombia TriStar Home Video, 2000)
Jeff Bridges is the prime suspect and Glenn Close plays the attorney who falls in love with him. When a San Francisci socialite is viciously murdered, her publisher-husband, Jack Forrester (Bridges), is accused of comitting the crime. Teddy Barnes (Close) decides to defend the charming, manipulative Jack, only to disregard legal ethics by having an affair with him. With the help of private eye Sam Ransom (Robert Loggia), she takes on a ruthless D.A. (Peter Coyote) who's using the case as a political steppingstones. However, a starting revelation puts Teddy in jeopardy of becoming the next victim of Jagged Edge.
Originally released as a motion picture in 1985
Written by Joe Eszterhas ; music by John Barry
Cast : Glenn Close, Jeff Bridges, Peter Coyote, Robert Loggia
Keywords: Trials (Murder) -- San Francisco -- Drama